Histomorphological Studies of Liver in Buffalo (Bubalus bubalis) - Thakur, Pravin Narayan; Kapadnis , P. J.; Saran, Devendra (International Journal of Livestock Research, 2019)
The histomorphological studies on the 24 buffalo livers (12 male and 12 female) were carried out. The liver was externally covered by dense white fibrous connective tissue (capsule). From the capsule originate the interlobular septae. The parenchyma of the liver was formed of hepatic lobules. Each lobule comprised of the cords of hepatocytes, which separated from each other by sinusoids. In each hepatic lobule, the plates of hepatocytes and sinusoids were appeared to be radiated outward from the central vein to the periphery of the liver lobule. Hepatocytes were polyhedral shaped cells, characterized by a centrally located spherical nucleus with chromatin granules and distinct cell membrane. The cytoplasm showed the dirty stained mitochondria. The lumen of sinusoids was lined by Von-Kupffer cells and endothelial cells. Bile canaliculi were observed in between two adjacent hepatocytes. As the bile duct enlarges from bile canaliculi to the hepatic duct, the epithelium appeared more columnar. The portal triad consisted of interlobular branches of hepatic artery, portal veins, interlobular bile duct, small lymphatic vessels and nerves. Collagen fibers were observed in the capsule, interlobular connective tissue and blood vessels, elastic fibers were observed in the capsule, interlobular connective tissue and blood vessels and the reticular fibers were observed in the capsule, interlobular septa and sinusoids of the liver in both male and female buffaloes.